Exploring Nexus Between Spiritual Intelligence and Leadership Success of BES JA’s President - Tsaniyah, Rohmatus; Huda, M. Nurul (http://jagadalimussirry.com/, 2020)
Abstract. Leadership is the ability to influence a group towards achieving goals. A leadership certainly has a benchmark of leadership success which will further be referred to as an indicator of leadership success, which is certainly related to the course of the organization during his leadership. The success of leadership is caused by several factors, one of which is spiritual intelligence. The purpose of this study is to describe the spiritual intelligence of President BES JA, the success of President BES JA's leadership, and the relationship between the two. This research is a descriptive type of research with a qualitative approach. The subjects of this study were the three old Presidents of BES JA. The results of this study are that the President of BES JA has a good relationship with Allah SWT and relations with fellow human beings and their leadership at BES JA in each period is considered quite successful in developing work programs, formulation and implementation of the regulations of the cottage, and the way BES JA stewardship wheels. And there is a link between spiritual intelligence and leadership success.